Built-in Self Repair Approach by Module Relocation for FPGA Based Reconfigurable Systems. (2016) - Eapen, Madhuri Elsa; Pradeep, C.; Varghese, Anila Ann; Nair, Jisha M.
Abstract: Systems that are installed in harsh environment conditions are continuously exposed to radiations, temperature variations and pressure variations which cause fast circuit degradation and malfunctioning. FPGAs are used as the core component in many such systems especially in mission critical and safety critical applications. To ensure reliable and prolonged system functioning until mission completion, proper fault recovery techniques need to be incorporated in to the system during the design phase itself. Traditional self-repairing schemes utilize spare cells to replace faulty cells. So, the number of spare cells increases with the number of faults to be repaired which creates high area overhead. Dynamic runtime partial reconfiguration has been considered to be a promising technique that helps improve the flexibility and efficiency of FPGA based systems. The key concept behind self-repairing scheme discussed in this paper is faulty module relocation to enable better use of resources and scheduling of repair for different modules to maintain system operation until mission completion or up to the required lifetime with maximum efficiency. The paper presents an efficient self-repairing scheme for FPGAs which can handle higher number of faults with better resource utilization and lesser overheads.